Multi-Omics Analysis of the Expression and Prognosis for FKBP Gene Family in Renal Cancer - Sun, Zeqiang; Qin, Xin; Fang, Juanjuan; Tang, Yueqing; Fan, Yidong (Frontiers in Oncology, 2021)
Backgrounds: FK506-binding protein (FKBP) is a family of intracellular receptors that can bind specifically to immunosuppressant FK506 and rapamycin. Although FKBPs play crucial roles in biological processes and carcinogenesis, their prognostic value and molecular mechanism in clear cell renal cell carcinoma (ccRCC) remain unclear. Methods: Using the pan-cancer data from TCGA and public databases, we analyzed the expression and correlation in 33 tumor types. Survival analysis and Cox regression analysis were employed to explore the prognostic value of FKBPs. The relationship with tumor microenvironment and stemness indices were taken into account to evaluate the function of FKBPs. We constructed a risk score model to predict the prognosis of patients with ccRCC. The ROC curve was performed to further test the prognostic ability of our model. Nomogram, joint effects analysis, clinical relevance was performed to guide the clinician. Gene set enrichment analysis (GSEA) and cell line experiments were performed to investigate the function and molecular mechanisms of FKBPs in patients with ccRCC. Paired clinical specimens and multi-omics analysis were used to further validate and explore the impact factors of gene expression in ccRCC patients. Results: The expression levels of FKBP10 and FKBP11 in ccRCC tissues were higher than those in normal tissues. The expression alteration may due to the degree of DNA methylation. The increased expressions of FKBP10 and FKBP11 were associated with worse overall survival (OS). More importantly, GSEA analysis revealed that FKBP10 was mainly involved in cell metabolism and autophagy, whereas FKBP11 was mainly associated with immune-related biological processes and autophagy. Results of cell counting kit 8 (CCK8) and Transwell assays revealed that the knockdown of FKBP10 and FKBP11 inhibits proliferation, migration, and invasion of ccRCC cell line. Conclusion: FKBP10 and FKBP11 play important roles in the phenotypes of ccRCC, and are potential prognostic markers as well as new therapeutic targets for patients with ccRCC.